2020
DOI: 10.1111/avj.12931
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous vitamin K1 normalises prothrombin time in 1 hour in dogs with anticoagulant rodenticide toxicosis

Abstract: Four dogs with anticoagulant rodenticide toxicosis were treated with intravenous vitamin K1 in lieu of plasma transfusion due to client cost constraints. Two dogs experienced a suspected anaphylactoid reaction, necessitating cessation of the treatment in one dog. Prothrombin time was rechecked 1 h after treatment in the remaining three dogs and all results were within the normal reference range. All four dogs were discharged from hospital within 48 h of presentation. Intravenous vitamin K1 rapidly reverses the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
5
0
4
Order By: Relevance
“…37 We encountered no adverse events associated with SC or IM vitamin K 1 administration but caution that IV administration should be avoided because of risk for anaphylactoid reaction. [38][39][40] Among cats with S-CCHS undergoing enteric or pancreatic biopsies, we confirmed IBD in 88% and pancreatitis in 93%. These are higher frequencies than previously reported for a small necropsybased study 6 of feline S-CCHS that reported 44% and 58% frequencies of IBD and pancreatitis, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…37 We encountered no adverse events associated with SC or IM vitamin K 1 administration but caution that IV administration should be avoided because of risk for anaphylactoid reaction. [38][39][40] Among cats with S-CCHS undergoing enteric or pancreatic biopsies, we confirmed IBD in 88% and pancreatitis in 93%. These are higher frequencies than previously reported for a small necropsybased study 6 of feline S-CCHS that reported 44% and 58% frequencies of IBD and pancreatitis, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…It is recommended that the vitamin K injections are subsequently followed by the oral administration of 2.5 mg/kg/q12h for seven days [ 32 ]. A recent study with 4 dogs describes intravenous administration of vitamin K to rapidly reverse the clotting factor deficiency; however, this may carry a substantial risk of anaphylactoid reaction [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another reported option for rapid provision of coagulation factors in these cases is through transfusion of a blood product containing plasma [ 34 ]. A blood transfusion was not performed in this case given that the administration of vitamin K1 IV has been shown to facilitate the restoration of coagulation factors in less time [ 33 ], which in turn has the potential to reduce the degree of haemorrhage and thus the subsequent neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Prothrombin is a serum clotting factor that is synthesized in the liver and dependent on vitamin K [5]. Factor Xa complex acts on prothrombin, breaking the two bonds on prothrombin, forming thrombin F1 and F2 (F1+2) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Prothrombin is a serum clotting factor that is synthesized in the liver and dependent on vitamin K [5]. Factor Xa complex acts on prothrombin, breaking the two bonds on prothrombin, forming thrombin F1 and F2 (F1+2) [5]. Thrombin F1+2 reflects the activity of factor Xa complex and is a specific molecular marker for the activation of prothrombin [6].…”
Section: Introductionmentioning
confidence: 99%